An Analysis Of Automatic Function Smoke Detection Tools Based On Arduino Uno - Mahrizal Masri; Hermansyah Alami; Armansyah, Armansyah (INFOKUM, 2024)
Electricity load forecasting is an estimate of the electricity load needs that will occur in the future based on existing data at present and in the past. This electricity load forecasting aims to avoid an electricity crisis which is also a crisis for electricity consumers whose average growth is increasing every year. This study discusses the implementation of the ant algorithm for electricity load forecasting with the MATLAB program. The method used is to implement data obtained from PT. PLN (Persero), Distribution and Load Regulation Center (P3B) of the North Sumatra Load Regulation Unit from February 1, 2012 to September 25, 2020. Ant algorithm using MATLAB program in this forecast is very helpful in implementing time series data so that a graphic visualization result will be obtained on the computer. Ant algorithm is a probabilistic technique adopted and inspired by the behavior of ant colonies known as ant systems.